2022
DOI: 10.3390/brainsci12060790
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status and Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is a complex and progressive neurodegenerative disease, characterized by resting tremor, rigidity, slowness of movement, and postural instability. Furthermore, PD is associated with a wide spectrum of non-motor symptoms that add to overall disability. In recent years, some investigations, from basic science to clinical applications, have focused on the role of vitamin D in PD, often with controversial findings. Vitamin D has widespread effects on several biological processes in the cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 118 publications
1
14
0
Order By: Relevance
“…This is further confirmed by the present study, which is in line with the available literature and with its heterogeneity ( 3 ). The latter is probably caused by differences in the demographic sample characteristics, in the outcome measures, and by the biological variability of the 25(OH)D and PTH metabolism over time, during seasons due to light exposure, but also age and sex ( 9 ). Our real-life study was conducted on a mild-to-moderate sample of patients with PD during the winter season when vitamin D levels are putative to be lower with a possible increase in PTH than in other periods of the year.…”
Section: Discussionmentioning
confidence: 99%
“…This is further confirmed by the present study, which is in line with the available literature and with its heterogeneity ( 3 ). The latter is probably caused by differences in the demographic sample characteristics, in the outcome measures, and by the biological variability of the 25(OH)D and PTH metabolism over time, during seasons due to light exposure, but also age and sex ( 9 ). Our real-life study was conducted on a mild-to-moderate sample of patients with PD during the winter season when vitamin D levels are putative to be lower with a possible increase in PTH than in other periods of the year.…”
Section: Discussionmentioning
confidence: 99%
“…A correlation between vitamin D levels, neurodegenerative diseases, and cognitive status is well-known in recent literature. For example, vitamin D levels are reported to be lower than expected values in Alzheimer's disease and other dementias [44,45] and in Parkinson's disease (PD) [46,47], where lower levels of vitamin D can represent a biomarker of risk of mild cognitive impairment (MCI) development in PD patients [48]. Furthermore, improvements in cognitive functions have been reported after supplementation in patients with MCI and Alzheimer's disease [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been shown that decreased levels of vitamin D leads to apoptosis of dopaminergic neurons, while its systemic administration counterbalances the process ( 55 ). In addition, growing evidence suggests that vitamin D may become a feasible biomarker for PD, but larger cohort studies are required ( 56 ).…”
Section: Appraising the Risk Of Heart Disease In Patients With Pdmentioning
confidence: 99%